Effectiveness of interventions designed to promote patient involvement to enhance safety: a systematic review. Issue 5 (27th April 2010) - Hall, Jill; Peat, Maggie; Birks, Yvonne; Golder, Su; Entwistle, Vikki; Gilbody, Simon; Mansell, Peter; McCaughan, Dorothy; Sheldon, Trevor; Watt, Ian; Williams, Brian; Wright, John
Abstract : Background: There is growing international interest in involving patients in interventions to promote and support them in securing their own safety. This paper reports a systematic review of evaluations of the effectiveness of interventions that have been used with the explicit intention of promoting patient involvement in patient safety in healthcare. Methods: The authors searched Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, CENTRAL, CINAHL, EMBASE, HMIC, MEDLINE, MEDLINE in-process, PsycINFO and ASSIA to August 2008. We also searched databases of reports, conference proceedings, grey literature, ongoing research and relevant patient safety organisations, and hand-searched two journals. Meta-analysis of the data was not appropriate; therefore, studies were categorised according to how the interventions encouraged patients' actions to improve safety—informing the management plan, monitoring and ensuring safe delivery of treatment (by health professional and by self), making systems safer—and were critiqued in a narrative manner. Findings: The authors identified 14 individual experimental and quasiexperimental studies plus one systematic review. The majority of studies fell into the monitoring and ensuring safe delivery of treatment by self category and were all related to enhancing medication safety. Authors reported improved patient safety incident outcomes for the intervention groups compared with controls where the interventions aimed to encourage patient involvement in: (1) monitoring and ensuring safe delivery of treatment by self (self-management of anticoagulation, 'easy' read information leaflet, nurse-led education to promote self-medication in hospital, patient package insert using lay terminology); (2) informing the management plan/monitoring and ensuring safe delivery of treatment by self (individualised teaching plan by nurse, pharmacist counselling). It was not possible to draw any clear conclusions as to the effectiveness of the interventions (with the exception of one specific aspect of self-medication, that is, self-management of anticoagulation) due to concerns about the methodological quality of the studies. Conclusions: There is limited evidence for the effectiveness of interventions designed to promote patient involvement on patient safety incidents and in general is poor quality. Existing evidence is confined to the promotion of safe self-management of medication, most notably relating to the self-management of oral anticoagulants.